HPDA/Zn as a CREB Inhibitor for Ultrasound Imaging and Stabilization of Atherosclerosis Plaque†. Issue 2 (10th December 2022) - Chen, Linzi; Jiang, Zhenqi; Yang, Lifei; Fang, Ye; Lu, Shuwei; Akakuru, Ozioma U.; Huang, Shuaishuai; Li, Juan; Ma, Suya; Wu, Aiguo
Comprehensive Summary: Thrombosis, secondary to rupture of unstable plaque, is a fatal risk factor for myocardial infarction and ischemic stroke. At present, more novel methods are needed for the diagnosis and treatment of vulnerable plaque. Here, we report a hollow polydopamine/Zn (HPDA/Zn) ultrasound contrast agent. Through western‐blot, Elisa, and other experiments, we found that in addition to having a good contrast‐enhancement capability in ultrasound imaging in vitro and in vivo, HPDA/Zn also has the effect of reducing the expression of CREB. CREB protein and its downstream‐regulated proteins and factors are closely related to the stability of plaque. HPDA/Zn has the effect of reducing the expression of CREB protein, which leads to the decrease of expression of MMP‐9, the regulatory protein downstream of the CREB protein. In addition, it also reduces the secretion of inflammatory factors hs‐CRP and IL‐17A. Thus, HPDA/Zn can stabilize plaque by inhibiting CREB and reducing plaque vulnerable markers and inflammatory factors. In a word, HPDA/Zn is a kind of ultrasound contrast agent, which can stabilize plaques by inhibiting CREB protein. Abstract :